The Slightest Attachment When Psychiatric Spaces Enact Affinities - d'Hoop, Ariane (VerKörperungen/MatteRealities - Perspektiven empirischer Wissenschaftsforschung, 2023)
While the disciplinary architecture of hospitals has long prevailed in psychiatry, many care teams now work in smaller structures, within communities. Ariane d'Hoop explores one of these places: Drawing on fieldwork in a psychiatric day center for teenagers, she traces how spatial arrangements matter in the care practice. From a corner in which one can withdraw, to a kitchen inviting to hang around, or displayed artworks that pique one's curiosity, caregivers use the material environment to stir up the slightest affinity from teenagers. This study thus expands our idea of what attachment is, and makes us more able to recognize the subtle dynamics between care, things, and spaces. With a preface by Jeannette Pols.